Impact of Membrane Pore Size on the Clarification Performance of Grape Marc Extract by Microfiltration - Francisca Mora; Karla Pérez; Carolina Quezada; Carla Herrera; Alfredo Cassano; René Ruby-Figueroa (Membranes, 2019)
The influence of membrane pore size on the permeate flux, fouling mechanism, and rejection of soluble and suspended solids, as well as of phenolics and anthocyanins, in the clarification of grape marc extract by microfiltration (MF) was studied. MF was operated by using three monotubular ceramic membranes with a pore size of 0.14, 0.2, and 0.8 µm, respectively, according to a batch concentration configuration in selected operating conditions (2.25 bar as operating pressure, 4.93 L/min as feed flow rate, and 25 °C as operating temperature). No significant differences in the permeate flux values were appreciated despite the difference in pore size. The mathematical analyses of the flux behavior revealed that intermediate pore blocking is the predominant mechanism for 0.14 and 0.2 µm membranes, whereas complete pore blocking prevails for the 0.8 µm membrane. Differences in the fouling mechanism were associated with differences in the total phenols rejection: the highest rejection was observed for the 0.8 µm membrane followed by 0.2 and 0.14 µm membranes. All selected membranes showed low rejection of sugars, with values lower than 10%, and no retention towards anthocyanins. All the clarified extracts showed a turbidity lower than 4.87 NTU. Based on the experimental results, the 0.14 µm membrane appeared as the best option for the clarification of grape marc extract.